Analysis of The Implementation of Online Referral for National Health Security Participant At PKU Muhammadiyah Karanganyar Hospital - Iik Sartika; Ahyar Mahasin (STRADA : Jurnal Ilmiah Kesehatan, 2020)
This research is kualitatif with the approach of case studies. This research was conducted in April-August 2019 at PKU Muhammadiyah Karanganyar Hospital, with in-depth interviews and observations related to implementation, obstacles, supporting factors, and policies related to online referrals. The results of the study showed the compatibility between the results of the implementation in the field compared with existing regulations. Implementation has met the needs of human resources and infrastructure, the flow stage is in accordance with Permenkes number 01 of 2012, obstacles that arise due to the delegation of focused authority, supporting factors, namely good coordination between units, and policies on SOP regarding full referral which do not regulate in detail about implementing online referrals. Recommendations based on this research, it is hoped that an evaluation of the implementation of the National Health Insurance policy on online referrals at PKU Muhammadiyah Karanganyar Hospital and improve services will be better